The prevalence of non-alcoholic fatty liver disease and its relationship with diabetes among patients attending the ultrasound unit in the Brak Al-Shati area. (Sebha University Conference Proceedings, 2025)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is defined as the accumulation of fat in liver cells of ≥ 5% in the absence of alcohol consumption or other liver diseases. NAFLD is strongly associated with several metabolic risk factors, including obesity, type 2 diabetes mellitus, insulin resistance, and both genetic and environmental influences. Objective: This study aims to determine the prevalence of this disease among patients visiting the ultrasound unit at Al-Sarah Clinic in the Brak Al-Shati area, as well as to determine the relationship between this Non-alcoholic fatty liver disease and diabetes. Materials and methods: The study was conducted from 20/5/2023 and 31/3/2024. Among approximately 400 patients who underwent abdominal ultrasound, 82 participants (50 with NAFLD and 32 without) aged 30–70 years were evaluated. Clinical and laboratory assessments included anthropometric measurement, and biochemical parameters (liver function tests, lipid profile, total protein, albumin, Fasting blood sugar, and HbA1c). Results: The prevalence of NAFLD among the study participants was approximately 24.75%, with a higher occurrence in females (69.7%) compared to males (30.3%), Significant differences were observed between the NAFLD and non-NAFLD groups in several anthropometric measurements, Moreover, elevated mean levels of Fasting blood sugar (FBS), HbA1c, total protein (TP), albumin (ALB), cholesterol (CHO), triglycerides (TG), and gamma-glutamyl transferase (GGT) were observed in the NAFLD group. A positive correlation was found between fasting glucose levels and variables such as waist-to-hip ratio, .HbA1c, alanine aminotransferase (ALT), and TG. These differences were statistically significant (p < 0.05). Conclusion: The findings highlight a high prevalence of NAFLD, especially among women, with a strong correlation between the disease and blood sugar levels